Arabic Language Learning Strategies at MTs 2 Nurul Islam Mojokerto: Implementation of Adaptive Pedagogy-Based Roleplay to Accommodate Differences in Student Learning Styles - Fahraini, Sovia; Afyuddin, Moh Sholeh (Proceeding International Conference on Education, 2025)
Every student has a different learning style, so Arabic language learning needs to be tailored to their needs. Adaptive pedagogy adapts learning to students' needs, and roleplay supports this by practicing Arabic contextually and interactively according to each student's learning style. Classroom Action Research (PTK) or Classroom Action Research reflective in nature with the aim of improving direct learning practices in the classroom. The research subjects were 33 bilingual eighth grade students and Arabic teachers at MTs 2 Nurul Islam. Data were collected through observation, interviews, and documentation, then analyzed using qualitative analysis techniques. So the results of its implementation are: a) Identification of student learning styles shows 15 visual students who learn effectively through images and visual media, 8 auditory students who understand the material through listening and discussion, and 10 kinesthetic students who learn optimally through direct practice and physical activity. Teachers need to apply diverse methods so that all learning styles are served. b) Innovative strategies in adaptive pedagogy through professional role-playing accommodate all learning styles through costumes, pronunciation, and physical activity in one fun activity. c) The impact of adaptive pedagogy on student learning styles is increased engagement, understanding, and learning comfort according to student characteristics. d) Challenges of adaptive pedagogy include adjusting learning styles, time management, student activity, and media limitations. The solution is to provide dialogue templates, visual-audio guides, and a gradual schedule.